PARENTS ATTITUDE TO AGGRESSIVE BEHAVIOR OF THE CHILDREN IN THE FAMILY - Kairiene, Brigita; Banyte, Gintare (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of pre-school children is very intensive and distinguishes itself by development periods with the expression of the features that are peculiar to them and which their parents are not always able to recognize and react appropriately and be in keeping with needs of the children. Therefore, a danger arises for a child to suffer non-adequate reaction, even aggression from his parents. The research aims to uncover parents’ attitude to pre-school children aggressive behavior in a family. 180 parents of 2-6 year old children attending Lithuania Raseiniai town pre-school training institutions participated in the research. The research revealed that parents unduly understand and interpret behavior that is typical for pre-school age children regarding it as aggressive. An inappropriate interpretation of child’s behavior induces parents to take up inadequate measures for correcting such behavior. More than one third of parents state that physical punishment can sometimes be effective means to educate children.